(untitled) (Journal of Statistics on Health Decision, 2021)
This article is an update of a systematic review and meta-analysis related to BMI levels in patients with multiple sclerosis. 31 studies published between 1997 and 2020 were collected. The main objective of this meta-analysis was to compare BMI levels between patients with MS and healthy controls. We conclude that BMI appears to be significantly lower in patients with MS, compared to healthy controls. However, after a more detailed analysis of the available data, it was realized that there are studies that are not very consistent, affecting the heterogeneity of the analysis. This heterogeneity may be associated with several external factors, such as alcohol and tobacco consumption, which were not taken into account in all included studies. In addition to this, there are still other limitations to consider, due to the lack of detailed information on the characteristics, such as the type of MS, the duration of the disease, the EDSS score or ethnicity, among others. After reducing this heterogeneity it was concluded that contrary to what is described in the literature, BMI does not present significant differences between patients with MS and healthy controls.